Weak Forms of Continuity and Associated Properties - Mohammad S. Sarsak (International Journal of Mathematics and Mathematical Sciences)
We introduce slightly 𝑝-continuous mapping and almost 𝑝-open mapping and investigate the relationships between these mappings and related types of mappings, and also study some properties of these mappings.